Respuesta :
y = 16x - 9
y = -4x + 21
16x - 9 = -4x + 21
16x + 4x = 21 + 9
20x - 30
x = 30/20 ...reduces to 3/2
y = -4x + 21
y = -4(3/2) + 21
y = -6 + 21
y = 15
solution is (3/2 , 15)
y = -4x + 21
16x - 9 = -4x + 21
16x + 4x = 21 + 9
20x - 30
x = 30/20 ...reduces to 3/2
y = -4x + 21
y = -4(3/2) + 21
y = -6 + 21
y = 15
solution is (3/2 , 15)
Answer: (1.5, 15)
Step-by-step explanation:
The given system of equations :-
[tex]y=16x-9...................(1)\\\\y=-4x+21..................(2)[/tex]
Substituting the value of y from equation (1) in equation (2), we get
[tex]16x-9=-4x+21[/tex]
Now, Adding 4x and 9 on both the sides , we get
[tex]16x+4x=21+9\\\\\Rightarrow\ 20x=30\\\\\Rightarrow\ x=\dfrac{3}{2}=1.5[/tex]
Substitute the value of x in equation (1), we get
[tex]y=16(1.5)-9=15[/tex]
Hence, the solution to the given system of equations : (1.5, 15)